Diabetes mellitus: A review of its associations with different environmental factors - Joshi, SK; Shrestha, S (Kathmandu University Medical Journal, 2010)
Diabetes Mellitus is a global health problem with a worldwide prevalence of 2.8% in 2000. Type 1 diabetes mellitus is an auto immune disorder genetically mediated, while type 2 is more of a life style induced disorder although the role of genetic susceptibility, infections are also equally strong. Many studies have backed up these statements. However, there have been very few researches that show association of diabetes with environmental factors like pollution, exposure to chemicals e.g. mercury, arsenic, psychological condition e.g. depression, stress, and socio-economic conditions e.g. occupation, earnings etc. Recently, the role of these factors in causation and progression of diabetes have received much attention. Thus, this review has been designed to explore more on association of diabetes with physical, socio-economic and psychological environment. Key words: arsenic; diabetes; environment; mercury; occupation; POPs; sleep; socio-economic status; stress DOI: 10.3126/kumj.v8i1.3233 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 109-115